Rancang Bangunmedia Pembelajaran Pengenalan Museum Mulawarman Berbasis Desktop - Muhammad Awang Ghozali; Damar Nucahyono; Yusni Nyura (JURNAL VOKASI TEKNIK, 2025)
"Learning Media Design Introduction To The Mulawarman Museum Desktop Based" is a learning media that carries the concept of introducing the history and artifacts at the Mulawarman Museum in the form of educational games. This game aims to increase access and interest of visitors, especially students and young people, towards museums. The main problem faced is the low interest in direct visits to museums. By designing learning media, players can learn while playing, creating an interactive and educational experience. The development of this learning media was carried out using Godot Engine 4.0 and the Game Development Life Cycle (GDLC) method to ensure structured stages, including initiation, pre-production, production, alpha testing, beta testing, and release. The results of this research are in the form of learning media that can provide information about the Mulawarman Museum to students and the younger generation, as well as preserving history through modern technology. This educational game not only functions as a learning tool but also as a medium to increase the attractiveness of the Mulawarman Museum in the digital era. With a score of 79.6%, this game was well received by young respondents aged 11-24 years, proving its success in providing information, ease of play, excitement, and increasing interest in visiting. This learning media is able to enrich history learning methods and foster cultural awareness among the younger generation, making museums more relevant and attractive for students and young people.